Interference of electron transfer chain inhibitors in bioelectrochemical systems - Hans Schneider; Bin Lai; Jens O. Krömer (Electrochemistry Communications, 2023)
Substances inhibiting specific proteins involved in cellular electron transfer chains are used in biochemical research to investigate intracellular electron transfer routes and to redirect the electron fluxes. This also provides an in vivo approach to investigating the extracellular electron transfer (EET) mechanisms within and across biological membranes in bioelectrochemical research. However, the applicability of these specific inhibitors in electrochemical systems remains to be validated, particularly when aiming for (semi-)quantitative evaluation of the contribution of specific redox proteins to the EET. Here we conducted a systematic analysis of commonly used inhibitors and discovered several of them to be electrochemically active and thus capable of interfering with measurements in a bioelectrochemical reactor system in abiotic experiments. We also observed effects in vivo using a biophotovoltaics reactor with Synechocystis sp. PCC 6803 as a model system.